Rugby drills 125 activities to improve your coaching sessions - Hogan, Eamonn (The Crowood Press, 2014)
Crowood's Rugby Drills is a collection of 125 activities, practices and games designed to improve coaching sessions at all levels of the game. The drills are organised into chapters according to a particular skill or phase of the game; from the warm up to handling, contact, lineout, scrum, kicking and defence. Each chapter starts with a series of simple activities before progressing through to more complex ones, each broken down into step-by-step explanations and diagrams, as well as guidance on how to increase the level of difficulty.